2014
DOI: 10.1055/s-0034-1376180
|View full text |Cite
|
Sign up to set email alerts
|

Does Increase in Birth Weight Change the Normal Labor Curve?

Abstract: We have shown that in a large cohort of contemporary laboring women, as birth weight increases, progression in labor is, in fact slower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In studies of labor 6 decades ago, Friedman found an large increase in the length of active nulliparous labor with increasing birthweight [27], but this association was much weaker among multipara [28]. This association was also found in the work of Nesheim [13] and in a large study which included women who delivered singleton, cephalic babies with gestational age >34 weeks at 19 hospitals in the United States [6]. This recent study analyzed birthweight in 0.5-kg increments and found that birthweight of more than 3 kg apparently became a factor in prolonging labor in multiparous women.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In studies of labor 6 decades ago, Friedman found an large increase in the length of active nulliparous labor with increasing birthweight [27], but this association was much weaker among multipara [28]. This association was also found in the work of Nesheim [13] and in a large study which included women who delivered singleton, cephalic babies with gestational age >34 weeks at 19 hospitals in the United States [6]. This recent study analyzed birthweight in 0.5-kg increments and found that birthweight of more than 3 kg apparently became a factor in prolonging labor in multiparous women.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies have examined the total length of the stages or phases of labor, or the median time of dilation in 1-cm integers (traverse time) [4, 68]. However, there is little consensus on the definitions of labor onset or the transition from latent to active phase [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leftwich et al [30] have shown that in a large cohort of contemporary laboring women, as birth weight increases, progression in labor is, in fact slower. In the present study, in nulliparous women, there were significant differences in the length of first stage of labor, active phase, the second stage of labor, and total labor duration among the different neonatal birth weight groups.…”
Section: Discussionmentioning
confidence: 99%